ChemInform Abstract: Deproto‐Metallation Using a Mixed Lithium—Zinc Base and Computed CH Acidity of 1‐Aryl 1H‐Benzotriazoles and 1‐Aryl 1H‐Indazoles. Issue 26 (1st July 2014) - Nagaradja, Elisabeth; Chevallier, Floris; Roisnel, Thierry; Dorcet, Vincent; Halauko, Yury S.; Ivashkevich, Oleg A.; Matulis, Vadim E.; Mongin, Florence
Abstract In the indazole series, the title reaction leads to ring opening of the heterocycle in general.